2014
DOI: 10.1073/pnas.1409778111
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the lipid profile in lymphomas induced by MYC overexpression

Abstract: Overexpression of the v-myc avian myelocytomatosis viral oncogene homolog (MYC) oncogene is one of the most commonly implicated causes of human tumorigenesis. MYC is known to regulate many aspects of cellular biology including glucose and glutamine metabolism. Little is known about the relationship between MYC and the appearance and disappearance of specific lipid species. We use desorption electrospray ionization mass spectrometry imaging (DESI-MSI), statistical analysis, and conditional transgenic animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
109
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 49 publications
10
109
1
Order By: Relevance
“…To evaluate whether these pathways have therapeutic value, we performed pharmacological inhibition of glutaminase, which converts glutamine to glutamate for its further oxidation through the TCA cycle. The inhibition of glutaminase by bis-2-(5-phenylacetamido-1,2,4-thiadiazol-2-yl)ethyl sulfide (BPTES) (27) slowed RCC tumor progression, suggesting that targeting the glutaminolytic pathway is a potential therapeutic approach to treat human RCC (24,25).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate whether these pathways have therapeutic value, we performed pharmacological inhibition of glutaminase, which converts glutamine to glutamate for its further oxidation through the TCA cycle. The inhibition of glutaminase by bis-2-(5-phenylacetamido-1,2,4-thiadiazol-2-yl)ethyl sulfide (BPTES) (27) slowed RCC tumor progression, suggesting that targeting the glutaminolytic pathway is a potential therapeutic approach to treat human RCC (24,25).…”
Section: Significancementioning
confidence: 99%
“…We used high-mass resolution and high-mass accuracy desorption electrospray ionization-massspectrometric imaging (DESI-MSI) and molecular biology methods to investigate the changes in metabolites, lipids, proteins, and genes in our RCC model. We used this approach because we previously described the successful use of DESI-MSI and transgenic mouse models to examine the lipid profiles of MYC-induced hepatocellular carcinomas (HCCs) (24) and lymphomas (25).…”
mentioning
confidence: 99%
“…The lipid composition of tumors is also affected by dynamic processes, having been observed to vary with cell proliferation, apoptosis, and necrosis (9). Furthermore, a recent study has revealed distinct lipid signatures in MYC-or RAS-induced lymphoma, suggesting that the observable lipid profile can be related to specific oncogene expression (10). In addition to genotype specificity, evidence suggests that metabolic profiles are highly tissue specific (11).…”
Section: Introductionmentioning
confidence: 99%
“…DESI-MSI can rapidly evaluate the tissue metabolome in situ by simultaneously characterizing hundreds of lipids and metabolites. In the last 5 y, reports from our group (16)(17)(18)(19) and others (15,(20)(21)(22) have demonstrated the usefulness of DESI-MSI in viewing the metabolite and lipid distribution in tissue samples from cancers and other diseases. Global changes in metabolism are a cardinal feature of neoplasia (23, 24), and DESI-MSI can determine global metabolite levels and their spatial distributions across a tissue sample on a microscopic slide.…”
mentioning
confidence: 99%